Evaluation of the Role of Digital Financial Literacy in Improving the Welfare of Micro, Small, and Medium Enterprises in Simalungun Regency, North Sumatra Province - Bayu Wulandari; Herlin Munthe; Tina Novianti Sitanggang; Jhon Lismart Benget; Agung Sahbana; Merry Rusida; Nagian Toni; Namira Ufrida Rahmi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital financial literacy is the ability of individuals to understand, evaluate, and use digital financial products and services effectively, efficiently, and safely. In the context of MSMEs, this literacy is important to help make the right decisions related to capital management, transaction recording, and more accurate business planning. This community service activity uses a participatory and educational approach. The participatory approach was chosen to actively involve MSME actors in the entire series of activities, while the educational approach aimed to improve the understanding, skills, and attitudes of MSME actors towards digital financial literacy. The PKM activity will be held on November 14, 2025 in Haranggaol Village, Simalungun Regency, North Sumatra Province. Based on the results of the evaluation that has been carried out, it can be concluded that digital financial literacy has a significant role in improving the welfare of Micro, Small, and Medium Enterprises (MSMEs) in Simalungun Regency, North Sumatra Province. MSME actors' understanding of the use of digital financial services, such as digital wallets, mobile banking, application-based financial recording, and non-cash transactions, has been proven to help improve the efficiency of business financial management.